MicroRNA-124 suppresses proliferation and glycolysis in non–small cell lung cancer cells by targeting AKT–GLUT1/HKII. Issue 5 (May 2017) - Zhao, Xiaojian; Lu, Caiping; Chu, Weiwei; Zhang, Bing; Zhen, Qiang; Wang, Renfeng; Zhang, Yaxiao; Li, Zhe; Lv, Baolei; Li, Huixian; Liu, Jiabao
Non–small cell lung cancer accounts for 85% of all types of lung cancer and is the leading cause of worldwide cancer-associated mortalities. MiR-124 is epigenetically silenced in various types of cancer and plays important roles in tumor development and progression. MiR-124 was also significantly downregulated in non–small cell lung cancer patients. Glycolysis has been considered as a feature of cancer cells; hypoxia-inducible factor 1-alpha/beta and Akt are key enzymes in the regulation of glycolysis and energy metabolism in cancer cells. However, the role of miR-124 in non–small cell lung cancer cell proliferation, glycolysis, and energy metabolism remains unknown. In this research, cell proliferation was investigated using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; furthermore, glucose consumption and lactic acid production were assessed; adenosine triphosphate content and NAD + /NADH were also detected. These tests were conducted using the normal non–small cell lung cancer cell line A549, which was transfected variedly with miR-mimics, miR-124 mimics, miR-124 inhibitor, pc-DNA3.1(+)-AKT1, and pc-DNA3.1(+)-AKT2 plasmid. Here, we show that miR-124 overexpression directly decreased cell growth, glucose consumption, lactate production, and energy metabolism. MiR-124 also negatively regulates glycolysis rate–limiting enzymes, glucose transporter 1 and hexokinase II. Our results also showed that miR-124 negatively regulates AKT1 and AKT2 but no regulatory effect on hypoxia-inducible factor 1-alpha/beta. Overexpression of AKT reverses the inhibitory effect of miR-124 on cell proliferation and glycolytic metabolism in non–small cell lung cancer. AKT inhibition blocks miR-124 silencing–induced AKT1/2, glucose transporter 1, hexokinase II activation, cell proliferation, and glycolytic or energy metabolism changes. In summary, this study demonstrated that miR-124 is able to inhibit proliferation, glycolysis, and energy metabolism, potentially by targeting AKT1/2–glucose transporter 1/hexokinase II in non–small cell lung cancer cells.